The Influence of Intimate Partner Violence on Pregnancy Symptoms - CAN GÜRKAN, ÖZLEM; EKŞİ GÜLOĞLU, ZÜBEYDE (SAGE PUBLICATIONS INC, 2020)
The current literature contains few studies conducted on the effects of intimate partner violence (IPV) on pregnancy symptoms. Does being subjected to IPV during pregnancy increase the incidence of pregnancy-related symptoms? The aim of the present study was to explore the impact of IPV on pregnancy-related symptoms. The study was conducted as comparative, descriptive, and cross-sectional research with a total of 370 participants. Data were collected using the Domestic Violence Against Women Screening Form, the Pregnancy Symptoms Inventory (PSI), and a descriptive questionnaire. The types of IPV the women in the study had experienced during pregnancy were, in order of frequency, verbal abuse (31.1 %; n = 115), economic abuse (25.9 %; n = 96), physical violence (8.4 %; n = 31), and sexual abuse (5.9%; n = 22). The PSI scores for the pregnant women subjected to physical violence related to gastrointestinal system symptoms (p < .05), cardiovascular system symptoms (p < .05), mental health symptoms (p = 0), neurological system symptoms (p < .05), urinary system symptoms (p < .01), and tiredness or fatigue (p = 0); their total PSI scores (p = 0) were significantly higher statistically than those of women who did not experience physical violence during pregnancy. The scores of the pregnant women subjected to sexual abuse related to mental health symptoms (p < .05), and their total PSI scores (p < .05) were significantly higher than those of women who did not experience sexual abuse. The scores of the pregnant women subjected to economic abuse related to tiredness or fatigue (p < .01) and their mental health symptom scores (p < .05) were significantly higher than those of women who did not experience economic abuse. Our results showed that women subjected to IPV during pregnancy experienced a higher incidence of pregnancy symptoms.
Keywords: intimate partner violence; violence against women; pregnancy; pregnant women; pregnancy symptoms; common discomfort of pregnancy; antenatal care; WOMEN; ANXIETY; ABUSE; RISK; PREVALENCE; OUTCOMES; HEALTH